HUBUNGAN ANTARA KARAKTERISTIK PETANI DENGAN PERSEPSI PETANI TERHADAP INOVASI PENERAPAN BURUNG HANTU TYTO ALBA SEBAGAI PENGENDALI HAMA TIKUS STUDI KASUS DESA GEMPOL KECAMATAN KARANGANOM KABUPATEN KLATEN - Yusrina Ulfah Ratnasih; Eny Lestari; Dwiningtyas Padmaningrum (Universitas Sebelas Maret, 2020)
The success of adopting Tyto alba as rat pest control in Gempol village because of not only positive farmers’perception but also farmers’characteristic. The Positive farmers’perception are linear to farmers’belief in adopting Tyto alba innovation for rat pest control. This study aimed to analyze: 1) farmers’ characteristic, 2) farmers’ perception, and 3) the relationship between farmers’ characteristic and farmers’ perception in adopting Tyto alba Barn owl innovation as rat pest control. This study was quantitative with a survey method and conducted in Gempol Village, Karanganom sub-district, Klaten, Central Java. It was chosen because the first village in Klaten uses Tyto alba as rat pest control. A total of sixty farmers were obtained with purposive random sampling. SPSS Statistics 17.0 with Spearman’s rank correlation was applied to make data analysis. The results showed that: 1) Farmers had a positive attitude, strong motivation, and skillful, also social environment were involved to the innovation of Tyto alba as rat pest control. 2) Farmers had a positive perception of the innovation of Tyto alba as a pest control. 3) There was a significant relationship between farmer attitude, motivation, and social environment to Tyto alba innovation as rat pest control. There wasn’t a significant relationship between farmer experience and perception in adopting Tyto alba as rat pest control.